2003
DOI: 10.1074/jbc.m300550200
|View full text |Cite
|
Sign up to set email alerts
|

The Mouse APG10 Homologue, an E2-like Enzyme for Apg12p Conjugation, Facilitates MAP-LC3 Modification

Abstract: Ubiquitylation and ubiquitylation-like protein conjugation mechanisms are essential to many cell-biological activities. Ubiquitin forms conjugates with target proteins via a threestep mechanism (1-3). First, ubiquitin is activated at its carboxyl-terminal glycine by the ubiquitin-activating (E1) 1 enzyme to form a conjugate through the active cysteine in the E1 enzyme via a thiol ester bond. Next, ubiquitin is transferred from the E1 enzyme to one of several ubiquitin-conjugating (E2) enzymes. In the last step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 37 publications
1
50
0
Order By: Relevance
“…These studies led to the identification of a set of Atg (autophagy related) factors, which are evolutionary conserved. 10,56,57 Two ubiquitin-like conjugation systems that participate in a coordinated manner are necessary in early stages of autophagosome formation [58][59][60] (see Box 2). The first conjugation system produces the Atg12-Atg5 complex that is non-covalently associated with Atg16.…”
Section: Biogenesis Of Mvbsmentioning
confidence: 99%
“…These studies led to the identification of a set of Atg (autophagy related) factors, which are evolutionary conserved. 10,56,57 Two ubiquitin-like conjugation systems that participate in a coordinated manner are necessary in early stages of autophagosome formation [58][59][60] (see Box 2). The first conjugation system produces the Atg12-Atg5 complex that is non-covalently associated with Atg16.…”
Section: Biogenesis Of Mvbsmentioning
confidence: 99%
“…1). [2][3][4][5][6][7][8] While Atg7 is a common E1 enzyme, Atg10 and Atg3 function as specific E2 enzymes for Atg12 and Atg8/LC3, respectively, to produce Atg12-Atg5 and Atg8-PE/LC3-PE conjugates, which are involved in the formation of autophagosomal membranes. 2,4,9,10 Atg5 is thought to be the sole target of Atg12, because immunoblotting anayses of Atg12 detect a single band of Atg12-Atg5 in addition to that of Atg12 alone.…”
mentioning
confidence: 99%
“…For example, mice with the heterozygous mutant autophagy gene ATG6/BECN1 are prone to developing liver and lung tumors (13)(14)(15)(16)(17). Atg7 is known to serve a role in forming the autophagic vacuole (15)(16)(17)(18)(19). Conversely, the protective mechanism of autophagy can be utilized by cancer cells to overcome environmental stresses, including nutritional deficiency and the therapeutic use of anticancer drugs (19).…”
Section: Introductionmentioning
confidence: 99%
“…It has been revealed that several autophagy-related (Atg) genes were involved in autophagosome formation (12)(13)(14)(15)(16)(17). Autophagy is a protective mechanism that exerts antitumor action (13)(14)(15)(16)(17). For example, mice with the heterozygous mutant autophagy gene ATG6/BECN1 are prone to developing liver and lung tumors (13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation